2021
DOI: 10.1186/s12920-021-01097-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of MTHFR C677T variant genotype with serum folate and Vit B12 in Iranian patients with colorectal cancer or adenomatous polyps

Abstract: Background The incidence of colorectal cancer (CRC) has increased during recent years in Iran and other developing countries. Clinical studies suggest that essential folate dietary intake and moderate deficiency of methylenetetrahydrofolate reductase (MTHFR) may protect and reduce the risk of CRC. The present study aimed to investigate the clinical significance of C677T polymorphism within the MTHFR gene and its correlation with the serum folate and Vit B12 in the Iranian population suffering f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
1
0
Order By: Relevance
“…Previous studies investigating the association of MTHFR rs1801133 and CRC have yielded conflicting results. Three studies conducted in Iran found that the MTHFR rs1801133 TT genotypes demonstrated a higher risk of CRC [ 32 34 ]. Baghad et al [ 35 ], Slattery et al [ 36 ], Ma et al [ 37 ], and Le Marchand et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating the association of MTHFR rs1801133 and CRC have yielded conflicting results. Three studies conducted in Iran found that the MTHFR rs1801133 TT genotypes demonstrated a higher risk of CRC [ 32 34 ]. Baghad et al [ 35 ], Slattery et al [ 36 ], Ma et al [ 37 ], and Le Marchand et al [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been suggested that ERCC1 is a potential anticancer drug target, the protein has no known enzymatic activity, making the means of regulating its activity harder to decipher [ 130 ]. Thus, currently targeted therapy regarding ERCC1 has evolved for MUTYH, which is a glycosylase involved in the BER pathway and associated with colorectal cancer, and for MTHFR, interacting with folate synthesis and being prognostic in various cancers [ 62 , 131 ].…”
Section: Discussionmentioning
confidence: 99%